Foreign Language Peace of Mind and Foreign Language Anxiety in Finnish Upper Secondary School students : A mixed-methods study - Koivumäki, Jatta (My University, 2023)
The present thesis examined the perceptions of Finnish upper secondary school students for Foreign Language Peace of Mind (FLPOM) and Foreign Language Anxiety (FLA). These two frameworks function in this study as support for one another, with FLA serving as the well-known framework while FLPOM is mapped out in a completely new context, that is Finnish upper secondary school. A wide variety of emotion constructs have been explored in the realm of Second Language Acquisition (SLA) thus far. Some emotion constructs have received significantly more attention than others. Furthermore, it is worth acknowledging that negative emotions have been studied to a much greater extent than positive emotions. This is why a novel positive emotion construct in the field of SLA is studied in this thesis, reinforced by FLA that has received substantial attention in the recent decades. FLPOM is a fresh concept in the field of SLA. It has only been applied into a small handful of target cultures and groups. As concept is very recent, no prior research on FLPOM in the Finnish foreign language learning context has been conducted. The current study functions as a pioneer in mapping out how the concept of FLPOM performs in a specific Finnish setting. The main objective of the study was to investigate Finnish upper secondary school students’ perceptions on the two emotion constructs. In addition, another objective was to unravel how the acquired knowledge on FLPOM and FLA could be feasibly utilised to further enhance FL learning and FL classrooms in the future. The participants were, in total, 30 Finnish upper secondary school students. Moreover, the data collection of the present study was executed through a questionnaire consisting of both open-ended items and Likert-scale based questions. The data were analysed both quantitatively and qualitatively. The mixed-method approach can be regarded as favourable as it allowed the collection of versatile data. The findings of this MA thesis indicate that FLPOM is an identifiable and beneficial element in foreign language learning for the Finnish learners. The participants have a slightly more precise understanding on the concept of FLA, however, the participants report quantitively experiencing considerably more of FLPOM than FLA. The described episodes of both emotions offer a thorough insight on the situations where the emotions are experienced as well as the participants comprehensibly explaining the effects of both concepts on their FL learning. The limitations of the study include the sampling of the participants, as the objective was to conduct the present study with a representable group of Finnish upper secondary school students, however, the participants were rather more internationally oriented and skilled at languages than expected. Research on FL emotions must continue in the future. Particularly interesting would be to implement FLPOM in more cultures and age groups, as well as studying the relationship between FLPOM and flow.
Keywords: Foreign Language Peace of Mind, Foreign Language Classroom Anxiety, Foreign Language Anxiety, peace of mind, emotions, emotional experience, positive psychology